Ferrol y Vigo en 1972. Historia y memoria de dos huelgas generales - José Gómez Alén (Cahiers de Civilisation Espagnole Contemporaine)
At the beginning of the 1970s, the major Spanish industrial centers experienced a wave of socio-labour conflict of great intensity that in the case of Galicia would culminate in the general strikes of 1972 in the districts of Vigo and Ferrol. The confrontations that went on for months at the Empresa Nacional Bazán in Ferrol were the starting point of a period of conflict that would persist throughout the year in the area of Vigo and would give rise to a general strike in which nearly 30,000 workers took part. This article traces the features of the strike process which in Ferrol reached a climax with the events of 10 March. Its repercussion went beyond Spanish borders and resulted in a broad movement of solidarity in Western Europe. What happened that day became the symbol of the Galician workers' struggle for democracy and is, at present, commemorated by the trade union organizations as the Day of the Galician Working Class and institutionally considered as such by the Galician Parliament.